Ultra-permeable CNTs/PES membranes with a very low CNTs content and high H2/N2 and CH4/N2 selectivity for clean energy extraction applications - Samy Yousef (Elsevier, 2021)
Polysulfone (PES) membranes are among the rare membranes that are capable of double filtration: a pre-filter layer captures agglomerates and a thin-dense layer is responsible for the main separation process. This work aims to enhance the permeability and H2/N2 and CH4/N2 of the dense layer of PES by mixing it with low concentrations of carbon nanotubes (CNTs: 0.01–0.03 wt.%) using solution casting and doctor blade techniques. The pore topology, microstructure, chemical, thermal, and mechanical properties of the synthesized CNTs/PES membranes were investigated using FTIR, XRD, TGA, and a universal testing machine, while permeability of single CO2, H2, N2, and CH4 permeability of the CNTs/PES membranes were tested under different temperatures (20–60 °C) and pressures (1–6 bar). Also, the effect of added CNTs, separation temperature, and pressure on the gas separation mechanism were investigated. The results showed that adding of CNTs contributed to increase in porosity from 81.7% (PES) to 88.4% (CNTs/PES) and decrease in pore sizes from 84 nm (PES) to 50 nm (CNTS/PES). Meanwhile, the thermal and mechanical analysis showed that CNTs/PES membranes had higher thermal stability and somewhat lower strength compared with neat membranes. Also, the permeability measurements showed a big increase when only 0.01 wt.% of CNTs had been added, where H2, CH4, N2, CO2 permeabilities were increased up to 28,553, 11,358, 7540, 6720 Barrer, respectively, vs 10.4, 4.6, 13.7, and 12.3 Barrer in case of PES membranes. In addition, CO2/N2, CH4/N2, and H2/N2 selectivity of CNTs/PES membranes were enhanced by 29%, 396%, and 426%, respectively, as a result of pores refining and increasing of free space in the prepared CNTs/PES membranes. According to these results, CNTs/PES membranes with small loading of CNTs have a tremendous ability to deal with separation of H2/N2 and CH4/N2, what make them promising candidates for clean energy extraction applications.